2014
DOI: 10.3109/14756366.2014.913036
|View full text |Cite
|
Sign up to set email alerts
|

3-Benzylidene-4-chromanones: a novel cluster of anti-tubercular agents

Abstract: In a quest for developing novel anti-tubercular agents, a series of 3-benzylidene-4-chromanones 1a-l were evaluated for growth inhibition of Mycobacterium tuberculosis H 37 Rv. Three promising compounds 1d, g, j emerged as the lead compounds with the IC 50 and IC 90 values of less than 1 mg/mL. Evaluation of the potent compounds 1d, g, j and k against Vero monkey kidney cells revealed that these compounds are far more toxic to M. tuberculosis than to Vero cells. Structure-activity relationships demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The homoisoflavonoids 21-24 were the next most active compounds, after compound 8. This class of natural products presents many biological properties, such as cytotoxic [49], antioxidant, anti-inflammatory [50], antibacterial [51], antiviral [52] and antifungal activity [53]. For the antifungal activity observed in this study, we evaluated the influence of the methoxyl substituent present in the B ring of derivatives 22, 23, and 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homoisoflavonoids 21-24 were the next most active compounds, after compound 8. This class of natural products presents many biological properties, such as cytotoxic [49], antioxidant, anti-inflammatory [50], antibacterial [51], antiviral [52] and antifungal activity [53]. For the antifungal activity observed in this study, we evaluated the influence of the methoxyl substituent present in the B ring of derivatives 22, 23, and 24.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that the presence of the methoxyl group at the meta position of the B ring contributed to the better antifungal bioactivity found for derivative 23. Das et al 2015 [51] evaluated analogues 22, 23, and 24, among other 3-benzylidene-4-chromanones derivatives, for anti-mycobacterial activity (Mycobacterium tuberculosis); to obtain potent anti-mycobacterial agents, the authors sug-gested the importance of inserting small substituent groups into the aromatic rings of the analog series under study. They also related the better bioactivity with the position of aromatic substituents in the B ring.…”
Section: Discussionmentioning
confidence: 99%
“…Kuete et al [86] isolated 5 polyphenols from twigs of Dorstenia barteri and screened them for antimycobacterial activity against M. Smegmatis and Mtb H 37 Rv strains. Among the polyphenols, 4-hydroxylonchocarpin (46) exhibited pronounced antimycobacterial activity (MIC=9.76µg/ mL) against both mycobacterial strains.…”
Section: Benzopyran-based Natural Products As Anti-tb Agentsmentioning
confidence: 99%
“…The compounds 7(a-d) showed moderate antitubercular activity with MIC values ranging between 10 and 12 µg/mL (Figure 5). Das et al [46] reported the synthesis of 3-benzylidine-4-chromanones and evaluated them for growth inhibition of Mtb H 37 Rv in BACTEC 12B medium and the growth inhibition was determined by the broth dilution assay [47]. Compound (8a) with a meta-bromo substituent on the benzylidine moiety showed highest inhibition (99%) at a concentration of 10µg/mL (Figure 5).…”
Section: Organic and Medicinal Chemistry International Journalmentioning
confidence: 99%
“…Figure 3: Basic chemical structures of the diferent types of homoisofavonoids found in nature. [6]; cytotoxicity against human cancer cell lines [7,8]; antidiabetic activity [9]; and antimicrobial activity [10][11][12][13][14][15]; among others [16,17]. Each year, fungal infections afect more than a billion people worldwide, with candidiasis representing about 75% to 88% of these infections.…”
Section: Caesalpin-type (Iv)mentioning
confidence: 99%